2007
DOI: 10.1007/s00704-007-0335-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impacts of land cover change in Amazonia: a regional climate model (RCM) simulation study

Abstract: SummaryThe numerical regional model (Eta) coupled with the Simplified Simple Biosphere Model (SSiB) was used to investigate the impact of land cover changes on the regional climate in Amazonia. Four 13-month integrations were performed for the following scenarios: (a) no deforestation, (b) current conditions, (c) deforestation predicted for 2033, and (d) large scale deforestation. All initial and prescribed boundary conditions were kept identical for all integrations, except the land cover changes. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 53 publications
6
41
1
3
Order By: Relevance
“…The relation between the increase in surface temperature and deforestation along the highways Belem-Brasilia, Cuiaba-Porto Velho, Manaus-Porto Velho is well indicated in the simulation. These values are close to those obtained by Correia et al (2008) where the authors evaluated the climate changes due to deforestation using the limited area ETA model. Numerical simulations with global circulation and regional model performed by Lean and Rowntree (1997) and Gandu et al (2004), respectively, have shown less significant increase, in the surface temperature, than obtained here.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The relation between the increase in surface temperature and deforestation along the highways Belem-Brasilia, Cuiaba-Porto Velho, Manaus-Porto Velho is well indicated in the simulation. These values are close to those obtained by Correia et al (2008) where the authors evaluated the climate changes due to deforestation using the limited area ETA model. Numerical simulations with global circulation and regional model performed by Lean and Rowntree (1997) and Gandu et al (2004), respectively, have shown less significant increase, in the surface temperature, than obtained here.…”
Section: Resultssupporting
confidence: 87%
“…The scenario of the 2050 year is elaborated from the dynamic vegetation model Dinamica EGO (SOARES-FILHO et al, 2004). In this study the biome degraded pasture represented the deforestation in the Amazon Basin (CORREIA et al, 2008). Many parameters have been calibrated using measurements taken on forest and pasture sites in the Amazon region (CORREIA et al, 2005).…”
Section: Deforestation and Ghg Emissions Scenariosmentioning
confidence: 99%
“…Four scenarios of LUC over the AMZ were analyzed by Correia, F.W.S. et al [22]: (a) no deforestation, (b) current conditions, (c) deforestation projected for 2033 and (d) large scale deforestation. For this investigation, 13-month integrations were performed using the Eta model (name derived from the Greek letter) coupled to the simplified simple biosphere model (SSiB).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the modelling studies addressing the impacts of LULC changes in South America are centred on tropical regions, particularly deforestation on the Amazon basin and desertification in northeast Brazil (e.g. Nobre et al, 1991;Hahmann and Dickinson, 1997;Baidya Roy and Avissar, 2002;Correia et al, 2007;Costa et al, 2007). Nevertheless, over the last two decades, A&R plans supported through government economic incentives or subsidies have been implemented in Chile, Uruguay, and Argentina (World Bank, 2000).…”
Section: Introductionmentioning
confidence: 99%